Evaluation Of The Guide Module For Integrated Holistic Teaching (Sains Humanika, 2015)
Enhancing quality education is the main agenda and intention of Malaysian’s education system.  The Malaysia’s National Education Philosophy (NEP) was established to produce a balance, holistic and harmonious human. However, in reality, social malaise among the young generation is getting worse despite the claim that schools and education have nurtured noble values in the young generation. Therefore, a more integrated and holistic approach is needed to improve the system.  So, the purpose of this study is to assess the implementation of the Integrated Holistic Teaching Guide Module among Technical and Vocational Education (TVE) trainee teachers in the Teachers Training Institute, Temenggong Ibrahim Campus. The objective of this module development is to expose, create awareness and appreciation among TVE trainee teachers on integrated holistic approach. This approach consists of eight activites which had been structured base on expertise opinion whereby trusted will guide TVE trainee teachers to be more balance, holistic, harmonious and responsible in implementing quality teaching process, as enshrined in the NEP. Indirectly, this will help the government to solve the social malaise among young generation. A pilot study was conducted with sixteen Design and Technology Semester 3 students. The collected data has been analyzed using Rasch Measurement Model to obtain the reliability of the participants in this reseach and the items. Result shows that Cronbach Alpha to measure participants’ reliability is 0.96, which is very high. Meanwhile the reliability for the instrument items is 0.69 which is at medium level. These items meet the range of infit / outfit Mean Square and the range of infit / outfit z-standard. Therefore, the Guide Module for Integrated Holistic Teaching achieved the objective of its development and perceived appropriate to be used.
Keywords: Quality teaching; national education philosophy; integrated holistic teaching; rasch model; Malaysia